Pengaruh Komite Audit, Likuiditas, Pergantian Auditor Dan Kompleksitas Operasi Terhadap Ketepatan Waktu Pelaporan Keuangan (Studi Pada Perusahaan Sub Sektor Perdagangan Besar (Grosir) Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2017-2019) - Widia Mey Krisyanti; Gede Adi Yuniarta (Universitas Pendidikan Ganesha, 2021)
This study analyses the effect of audit committee variables, liquidity, auditor turnover and operating complexity on the timeliness of financial reporting. The data used are secondary data in the form of annual reports and financial reports of large trading sub-sector companies (wholesale) listed on the Indonesia Stock Exchange in 2017-2019. The technique for selecting the sample used purposive sampling to obtain a sample of 22 companies. The data analysis used is descriptive statistics and logistic regression analysis with the SPSS 25 program. The results of this study state that liquidity has a positive and significant effect on the timeliness of financial reporting, while the audit committee, auditor turnover and operating complexity do not affect the timeliness of financial reporting.Keywords: Audit Committee, Liquidity, Auditor Turnover, Complexity Of Operations, Timeliness Of Financial Reporting.